Smart Medicine Pill Box Reminder - Azlan, Muhammad Alif Izzat; Yahya @ Atan, Roshayati (Evolution in Electrical and Electronic Engineering, 2023)
With the increase of elderly and young people who are diagnosed with diseases, the proper and correct medicines taken need to become the first priority to being healthy. However, among this people, 40-60% are having an issue of forgetting to take medicine on right time. The main objective of this project is to design a system that will alert the patients to take the medicines and also create an application that will alert the caretakers if their patients have taken the medicines by detecting the weight of the pill box. The system consists of a box where the patients will be able to keep their medicines and will alert the patients to take their medicines visually and audibly. The Blynk application will send a notification to notify the caretaker if the patients have taken their medicines. This system has a feature that uses a weight sensor to detect the remaining medicines that are present in the box. The caretaker will be notified if the status of the pill box is less than 50% of the total weight of the medicines through this application. By using the Blynk application the caretaker can get a notification about the status of the pill box hence knowing if their patients have taken their medicines in the following week. It can be seen that in order to reach 50% of the total weight of the medicines the patients have to take their medicines four times. This gives an indication to the caretakers that their patients have taken their medicines for four days. Some improvements that can be made are, by changing the working system of the load cell in order to detect the changes in weights of the medicines in the pill box for each day of the week.